Rancang Bangun Sistem Informasi Promosi Pariwisata Kecamatan Lepar Pongok Kabupaten Bangka Selatan - Zuhri, Zuhri; Josi, Ahmat; Andriyanto, Sidhiq (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Lepar Pongok District has 8 tourist attractions but what can be displayed on the website are 6 tourist attractions, information about tourist attractions in Lepar Pongok District is still lacking, due to the lack of information about tourism in Lepar Pongok District, so with this the author is interested in making